"Animal History after Its Triumph: Unexpected Animals, Evolutionary Approaches, and the Animal Lens". Issue 7 (July 2016) - Specht, Joshua
Abstract: Part of a broad animal turn in the humanities, animal history is now a large, mature field. Taking the triumph of animal history as a starting point, this essay draws from scholarship on a diversity of places and time periods to provide a state of the field. The discussion opens with an account of a central theme in animal history: the "animal lens." This lens uses animals to explore broad historical phenomena, from industrialization to ideas about gender. Next is a discussion of two recent trends in animal history: (1) scholarship on "unexpected animals" and (2) evolutionary history, which examines how humans have shaped animal bodies over time. The overview closes with a discussion of agency, suggesting that the field abandons this paradigm.